Chosen Aspects of Psychiatric Confidentiality in the Jurisprudence of the Supreme Court - Paweł Górski (Acta Universitatis Lodziensis Folia Iuridica)
Psychiatric secrecy, which is based on Article 50 of the Law of August 19, 1994 on Mental Health Protection, is intended to protect the dignity and privacy of patients and their families. However, it does not have an absolute character and can be limited or abrogated in certain situations, examples of which can be found in case law. Accordingly, the purpose of the article was to analyze the Supreme Court’s rulings on mental health issues and the protection of secrecy related to it. The article is an overview, analyzing the case law of the Supreme Court on the issue of psychiatric secrecy. The results of the analysis show that in the jurisprudence of the Supreme Court, the issue of psychiatric secrecy appears in the context of criminal proceedings, especially in cases related to the work of expert witnesses. The Court emphasizes that this secrecy is not absolute and may be subject to restrictions to protect other constitutional goods, but in proportion between the purpose of the restriction and the scope of the information disclosed. The Court’s rulings also emphasize the autonomy of psychiatric experts and the need to trust their professional competence, noting various aspects related to the evaluation of their work. Based on the analysis of the Supreme Court’s jurisprudence, it can be concluded that psychiatric confidentiality does not have an absolute character and can be limited in certain situations, but always with respect for the patient’s personal rights. The case law further indicates the need to balance this secrecy with other values, such as the welfare of the patient or society. It should also be noted that existing differences in the interpretation of the rules on the appointment of psychiatric experts in the criminal process may affect judicial practice in this area.